Gamma-patterned sensory stimulation reverses synaptic plasticity deficits in rat models of early Alzheimer's disease - O'Rourke, Eugene; Cunningham, Colm; Hu, Nengwei; Reilly, Richard; Rowan, Michael (My University, 2023)
Non-invasive sensory stimulation in the range of the brain’s gamma rhythm (30–100 Hz) is emerging as a new potential therapeutic strategy for the treatment of Alzheimer’s disease (AD). Here, we investigated the effect of repeated combined exposure to 40 Hz synchronized sound and light stimuli on hippocampal long-term potentiation (LTP) in vivo in three rat models of early AD. We employed a very complete model of AD amyloidosis, amyloid precursor protein (APP)-overexpressing transgenic McGill-R-Thy1-APP rats at an early pre-plaque stage, systemic treatment of transgenic APP rats with corticosterone modelling certain environmental AD risk factors and, importantly, intracerebral injection of highly disease-relevant AD patient-derived synaptotoxic beta-amyloid and tau in wild-type animals. We found that daily treatment with 40 Hz sensory stimulation for 2 weeks fully abrogated the inhibition of LTP in all three models. Moreover, there was a negative correlation between the magnitude of LTP and the level of active caspase-1 in the hippocampus of transgenic APP animals, which suggests that the beneficial effect of 40 Hz stimulation was dependent on modulation of pro-inflammatory mechanisms. Our findings support ongoing clinical trials of gamma-patterned sensory stimulation in early AD.
PUBLISHED
Keywords: 40 Hz sensory stimulation; Alzheimer’s disease aqueous brain extract; amyloid precursor protein transgenic rats; beta-amyloid; long-term potentiation; tau; Neuroscience; Age related diseases; Ageing, memory and other cognitive processes; Ageing, stroke, dementia; Neurodegeneration; Age-related disability; Mental Health/Psychosocial disability; Health